2008
DOI: 10.1007/s00277-008-0506-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of the haemochromatosis gene (HFE) variants C282Y, H63D and S65C in 6,020 ethnic Danish men

Abstract: The objective was to assess the frequencies of haemochromatosis (HFE) gene mutations or variants C282Y, H63D and S65C in ethnic Danes. This is a prospective epidemiologic population study. A cohort of 6,020 Danish men aged 30-50 years was screened for HFE C282Y (c845G-->A), H63D (c187C-->G) and S65C (c193A-->T) gene variants, assessed on saliva or blood samples by restriction fragment length polymorphism (RFLP) analysis. The C282Y gene variant allele was present in 5.6%, H63D in 12.8% and S65C in 1.8% of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…This study had a limited sample size and low frequency of this mutation affects benchmarks that allow more detailed conclusions. Similar data are also reported on the international scene because, for example, in China and South Korea, there is no indication of the presence of the mutant S65C allele (Lin et al, 2007;Lee et al, 2009); in Venezuela, the allelic frequency is 0.009 (Vizzi et al, 2005), while individuals with hemochromatosis in Denmark and Spain were found to have respectively allelic frequencies of 0.018 and 0.02 (de Diego et al, 2004;Pedersen et al, 2008 Table 2. Genotypic and allelic frequencies for S65C mutation, according to gender.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study had a limited sample size and low frequency of this mutation affects benchmarks that allow more detailed conclusions. Similar data are also reported on the international scene because, for example, in China and South Korea, there is no indication of the presence of the mutant S65C allele (Lin et al, 2007;Lee et al, 2009); in Venezuela, the allelic frequency is 0.009 (Vizzi et al, 2005), while individuals with hemochromatosis in Denmark and Spain were found to have respectively allelic frequencies of 0.018 and 0.02 (de Diego et al, 2004;Pedersen et al, 2008 Table 2. Genotypic and allelic frequencies for S65C mutation, according to gender.…”
Section: Discussionsupporting
confidence: 75%
“…Due to menstruation and pregnancy, HH occurs 2 to 4 times more in men than in women (Limdi and Crampton, 2004;US Preventive Services Task Force, 2006). Generally, HH appears between 40 to 60 years old, an age at which there is an excess of 20 to 40 g iron, accumulated slowly in the body throughout life (Pedersen et al, 2008), where the fifth decade is the most common age for the main signs and symptoms in women (US Preventive Services Task Force, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of genetic testing, it became clear that the mutation leading to the C282Y substitution is a commonly inherited trait in those of northern European extraction [39]. Most C282Y homozygote males will develop biochemical indices of iron loading [36,37,[40][41][42][43], but often this is not enough to lead to disease without comorbid factors [40] (Fig. 2).…”
Section: Penetrancementioning
confidence: 97%
“…Furthermore, iron overload disorders, i.e. HFE-related hemochromatosis, are the most frequent inherited disorders in subjects of northern European descent [26], and non-HFE-related hemochromatosis [27] is frequent in the Mediterranean.…”
Section: Strategies To Ensure An Adequate Iron Supply For Pregnant Womenmentioning
confidence: 99%